Kyoto and the carbon content of trade - Rahel Aichele; Gabriel Felbermayr (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2010)
A unilateral tax on CO2 emissions may drive up indirect carbon imports from non-committed countries, leading to carbon leakage. Using a gravity model of carbon trade, we analyze the effect of the Kyoto Protocol on the carbon content of bilateral trade. We construct a novel data set of CO2 emissions embodied in bilateral trade flows. Its panel structure allows dealing with endogenous selection of countries into the Protocol. We find strong statistical evidence for Kyoto commitments to affect carbon trade. On average, the Kyoto protocol led to substantial carbon leakage but its total effect on carbon trade was only minor.
urn:nbn:de:bsz:100-opus-4178
Keywords: F18; Q54; Q56; 330; Carbon leakage; gravity model; international trade; climate change; embodied emission; input-output analysis; Ökosteuer; Kohlendioxid; Emissionshandel; Außenhandel; Klimaschutz; Gravitationsmodell; Input-Output; Theorie; Welt